If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6y = -29 Solving x + -6y = -29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. x + -6y + 6y = -29 + 6y Combine like terms: -6y + 6y = 0 x + 0 = -29 + 6y x = -29 + 6y Simplifying x = -29 + 6y
| x=x^2-0.25 | | 4n-12=n-27 | | .55(F-32)=25 | | 0.125n+0.75=-0.125n-0.25 | | -6+8(x-3)=12x+6-4x | | (2x-3)-(2x-3)(x+1)-2(2x-3)=0 | | 5x+18=5x+15 | | (5-x)(2x+1)=18x | | -x-5y=-37 | | 9b=-72 | | 347.06=200+0.57x | | 20000=(x*.2)+x | | -3(5x+7)=-21 | | 7(1x+6)=28 | | 4*(n*-3)=n-27 | | 3(-r)+5= | | c^8-15625c^2=0 | | 12.0x+10=34+9.9x | | a^6+32a=0 | | c+c*c=0.24 | | 3x^6-x^3-24=0 | | 3x^2+3=x | | 59-4x=14x+19 | | 3w+(3w+36)=84 | | 9x^2y^2+9xy+2= | | 5x-10=98+6x | | x^2y^2-3xy+2=0 | | 93=11x+5 | | 8+5x-11=3x-22+9x | | 3z^2-8z-16=0 | | 32m^2+14n^2-8-12m^2+5n-3= | | 5x=230 |